Potential biocide roles of violacein - Rivero Berti, Ignacio; Gantner, Melisa E.; Rodriguez, Santiago; Islan, German A.; Fávaro, Wagner J.; Talevi, Alan; Castro, Guillermo R.; Durán, Nelson (Frontiers in Nanotechnology, 2023)
Violacein is a pigment produced by Gram-negative bacteria, which has shown several biological activities. The most relevant activities of violacein include the interference in the physiological activities of biological membranes, inhibition of cell proliferation, antioxidant, and anti-inflammatory activities. Moreover, the antiviral activities of violacein against some enveloped and non-enveloped viruses have also been reported. Violacein showed a wide spectrum of protease inhibition, both experimentally and in-silico. Other in silico studies have suggested that violacein binds to the SARS-CoV-2 spike. Empirical physicochemical studies indicate that violacein (or, occasionally, its derivatives) may be administered orally to treat different disorders. In addition, different alternatives to product violacein, and molecular devices for delivery of this pigment are reviewed